2009
DOI: 10.1002/fld.2147
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and stability analysis of laminar flow in curved ducts

Abstract: SUMMARYThe development of viscous flow in a curved duct under variation of the axial pressure gradient q is studied. We confine ourselves to two-dimensional solutions of the Dean problem. Bifurcation diagrams are calculated for rectangular and elliptic cross sections of the duct. We detect a new branch of asymmetric solutions for the case of a rectangular cross section. Furthermore we compute paths of quadratic turning points and symmetry breaking bifurcation points under variation of the aspect ratio ( = 0.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…In figure 2 we show schematically a portion of the bifurcation diagram found. It incorporates branches 1-8 which are solutions found in previous studies (Boshier & Mestel 2014;Machane 2010;Daskopoulos & Lenhoff 1989;McConalogue & Srivastava 1968) and reproduced here and branches 9-15 which are found for the first time in the current work. To ease visualisation, the diagram represents branches projected onto the real K 2 axis.…”
Section: Constructing Complex Solution Branchessupporting
confidence: 80%
See 2 more Smart Citations
“…In figure 2 we show schematically a portion of the bifurcation diagram found. It incorporates branches 1-8 which are solutions found in previous studies (Boshier & Mestel 2014;Machane 2010;Daskopoulos & Lenhoff 1989;McConalogue & Srivastava 1968) and reproduced here and branches 9-15 which are found for the first time in the current work. To ease visualisation, the diagram represents branches projected onto the real K 2 axis.…”
Section: Constructing Complex Solution Branchessupporting
confidence: 80%
“…As expected, this problem is found to exhibit many features similar to that of the circular pipe. Machane (2010) found multi-vortex solutions for elliptic cross-sections of aspect ratio λ = 1.45, though his bifurcation diagram differs from that found for the circular cross-section. Interestingly, in his study he concluded that the number of vortices on a particular branch may gradually change without running through a singular point, suggesting that 'number of vortices' is not a robust diagnostic for distinguishing between solutions in the elliptic case.…”
Section: Pipes Of Elliptic Cross-sectionmentioning
confidence: 55%
See 1 more Smart Citation
“…Recently, Watanabe and Yanase (2013) obtained various bifurcation structures for the threedimensional case and found a connection between the branches. Bifurcation diagram from small to large aspect ratio for different aspect ratios have been also calculated by Mechane (2010). Using Euler-Newton continuation method, Yang and Wang (2001) pointed out the position of the symmetric and asymmetric solution of branches.…”
Section: Introductionmentioning
confidence: 99%